Pengaruh Corporate Social Responsibility terhadap Profitabilitas dan reputasi perusahan pada perusahaan Perbankan yang terdaftar di BEI periode 2018–2020 - Syeren Al Gista; Dewi Prastiwi (Politeknik Ganesha Medan, 2022)
Corporate Social Responsibility (CSR) is an effort made by the company to improve the company's image in the social, economic and environmental fields by making positive activities that are internal or external. This study aims to determine and analyze whether there is an influence of CSR on the profitability and reputation of the company. The object in this study is the banking sub-sector companies listed on the Indonesia Stock Exchange for the 2018-2020 period. This research method uses quantitative methods, data collection techniques use documentation methods, and data analysis techniques use the MANOVA (Multivariate Analysis of Variance) analysis method using the SPSS 23 application. The independent variable used in this study is CSR (X) and the dependent variable in In this research, profitability (Y1) is proxied by ROA, ROE and company reputation (Y2) is proxied by Tobins'Q. The results of this study are that CSR has a significant effect on ROA, ROE and Tobins'Q in banking companies listed on the IDX for the period 2018-2020.